2007
DOI: 10.1016/j.technovation.2006.10.001
|View full text |Cite
|
Sign up to set email alerts
|

The importance of diverse collaborative networks for the novelty of product innovation

Abstract: Competition today is driving firms to introduce products with a higher degree of novelty. Consequently, there is a growing need to understand the critical success factors behind more novel product innovations. This paper theoretically and empirically analyzes the role of different types of collaborative networks in achieving product innovations and their degree of novelty. Using data from a longitudinal sample of Spanish manufacturing firms, our results show that technological collaborative networks are of cru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

38
725
3
74

Year Published

2008
2008
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 1,061 publications
(840 citation statements)
references
References 63 publications
38
725
3
74
Order By: Relevance
“…(Knoke and Kuklinski, 1982;Wasserman and Faust, 1994), the identification of relevant environmental conditions and how they influence the structure and functioning of networks has generally been ignored by social network theorists. Recently some studies have tried to shed more light on this and have indicated that the optimality of the network structure is indeed dependent upon the environmental context (Kogut, 2000;Rowley et al, 2000;Ahuja, 2000;Hagedoorn and Duysters, 2002;Nieto and Santamaria, 2007). Following this, we argue that the environmental context has profound implications for how an exploration network is structured and how it functions in view of novelty creation.…”
Section: Who Is Right Under Which Conditions?mentioning
confidence: 54%
See 1 more Smart Citation
“…(Knoke and Kuklinski, 1982;Wasserman and Faust, 1994), the identification of relevant environmental conditions and how they influence the structure and functioning of networks has generally been ignored by social network theorists. Recently some studies have tried to shed more light on this and have indicated that the optimality of the network structure is indeed dependent upon the environmental context (Kogut, 2000;Rowley et al, 2000;Ahuja, 2000;Hagedoorn and Duysters, 2002;Nieto and Santamaria, 2007). Following this, we argue that the environmental context has profound implications for how an exploration network is structured and how it functions in view of novelty creation.…”
Section: Who Is Right Under Which Conditions?mentioning
confidence: 54%
“…Bathelt et al, 2004). Although in this literature the importance of relations and interaction among heterogeneous firms and actors is clearly acknowledged (Nelson and Winter, 1982;Dosi et al, 1988;Nieto and Santamaria, 2007), an in-depth understanding of the structure and role of interfirm networks is still underdeveloped (Pavitt, 2002;Malerba, 2004). For a deeper understanding of networks we need to turn to the social network literature.…”
Section: Introductionmentioning
confidence: 99%
“…First, it relies on the patent licensing as the main channel to access external knowledge sources. There are other means through which external knowledge resources can be acquired, e.g., joint ventures, merger and acquisitions, and spillover effects from informal knowledge sharing (Ahuja & Katila, 2001;Vanhaverbeke, Duysters, Noorderhaven, 2002;Nieto & Santamaría, 2007). Future research is encouraged to investigate these alternatives and their impacts on dynamic capabilities and resource reconfiguration.…”
Section: Discussionmentioning
confidence: 99%
“…Faems, Van Looy and Debackere, 2005;Nieto and Santamaria, 2007;Porter and Ketels, 2003). Overall, a consensus has been developed that suggests that the exclusion of participation in such networks becomes a limiting factor for enhancing a firm's knowledge base (Shaw, 1998).…”
Section: Inter-firm Networkingmentioning
confidence: 99%